Outcome Comparison of Endoscopic (Endonasal Trans-Sphenoidal) Repairs of CSF Leak vs. Transcranial Approach - Mehran Ali; Naseer Hassan; Hamayun Tahir; Mansoor Ahmad; Samir Khan Kabir; Raza Hassan (Gandhara University, 2022)
OBJECTIVES: To compare the effectiveness of Endoscopic (endonasal transsphenoidal) repair of CSF leak with transcranial approach in terms of post-operative complications.  METHODOLOGY:   This study was conducted in the Department of Neurosurgery, Lady Reading Hospital, Peshawar. Total of 40 patients diagnosed according to inclusion criteria were enrolled and were divided into two groups. One group was treated with endonasal trans-sphenoidal repair, and another was treated with a trans-cranial approach. All patients were followed for 1 year.  RESULTS:  The mean age of enrolled patients was 35.4±11.6 years. There were 62.5% male and 37.5% female. In the endoscopic group the recurrence rate was observed in 3 (15%) of the patients while in the trans-cranial group the recurrence rate was observed in 2 (10%) of the patients. The overall recurrence and success rate was 8% and 92% respectively. About 4 patients developed an infection, which was treated successfully.  CONCLUSION:  It is concluded that the endoscopic approach is safe and effective. The endoscopic approach should be considered as standard procedure for treatment.